2016
DOI: 10.1261/rna.056077.116
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide specificity of the human terminal nucleotidyltransferase Gld2 (TUT2)

Abstract: The nontemplated addition of single or multiple nucleotides to RNA transcripts is an efficient means to control RNA stability and processing. Cytoplasmic RNA adenylation and the less well-known uridylation are post-transcriptional mechanisms regulating RNA maturation, activity, and degradation. Gld2 is a member of the noncanonical poly(A) polymerases, which include enzymes with varying nucleotide specificity, ranging from strictly ATP to ambiguous to exclusive UTP adding enzymes. Human Gld2 has been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 63 publications
2
42
0
Order By: Relevance
“…On the contrary, S. cerevisiae Trf4 and Trf5 proteins, displaying PAP activity (LaCava et al 2005;Vanacova et al 2005;Wyers et al 2005;Houseley and Tollervey 2006;Hamill et al 2010), contain DxxDxxN cluster at the equivalent position and the same is true for S. pombe nuclear noncanonical PAP, Cid14 (Table 1; Win et al 2006). Importantly, asparagine seems to be invariantly present in the last position of the NRM cluster in all noncanonical NTases, for which PAP activity has been experimentally demonstrated, including recently studied human GLD-2 (TUT2) which contains ExxDxxN cluster (Table 1; Chung et al 2016). In concordance, the Cid1 H336N mutation (creating DxxExxN cluster) changed Cid1 specificity from PUP into PAP (Lunde et al 2012).…”
Section: Discussionmentioning
confidence: 91%
“…On the contrary, S. cerevisiae Trf4 and Trf5 proteins, displaying PAP activity (LaCava et al 2005;Vanacova et al 2005;Wyers et al 2005;Houseley and Tollervey 2006;Hamill et al 2010), contain DxxDxxN cluster at the equivalent position and the same is true for S. pombe nuclear noncanonical PAP, Cid14 (Table 1; Win et al 2006). Importantly, asparagine seems to be invariantly present in the last position of the NRM cluster in all noncanonical NTases, for which PAP activity has been experimentally demonstrated, including recently studied human GLD-2 (TUT2) which contains ExxDxxN cluster (Table 1; Chung et al 2016). In concordance, the Cid1 H336N mutation (creating DxxExxN cluster) changed Cid1 specificity from PUP into PAP (Lunde et al 2012).…”
Section: Discussionmentioning
confidence: 91%
“…The active site regions of the PAPs and PUPs we identified bear on how U and A are distinguished by different enzymes in the same family. Prior work demonstrated that a histidine in the active-site regions of Human Gld2 and S. pombe Cid1 dictates their apparent preferences for A and U, respectively [62][63][64][65][66][67] . Similarly, U-adding enzymes appear to have arisen repeatedly in evolution by the insertion of histidine into ancestral A-adding enzymes 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior work demonstrated that a histidine in the active-site regions of Human Gld2 and S. pombe Cid1 dictates their apparent preferences for A and U, respectively [62][63][64][65][66][67] . Similarly, U-adding enzymes appear to have arisen repeatedly in evolution by the insertion of histidine into ancestral A-adding enzymes 62 . However, among the U-adding enzymes we uncovered here, several (Sp Cid16, Ce PUP-3 and Ce F43E2.1) lack that histidine, and one that possesses a histidine (Hs TUT1/Star-PAP) adds adenosines 21 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a histidine residue in Cid1 (His336), conserved in some plant and human cytosolic TUTases but absent from trypanosomal TUTases, has been involved in UTP selectivity . A single amino acid substitution at this position is sufficient to switch the specificity of Cid1 from UTP to ATP, and vice versa for human Gld2 (TUT2) . Those experiments illustrate the ease of switching the nucleotide specificity of a terminal nucleotidyltransferase during evolution to allow for the acquisition of a novel biological function linked to RNA tailing.…”
Section: Key Features Of Terminal Uridylyltransferasesmentioning
confidence: 94%